Central Auditory Processing Disorders in Individuals with Autism Spectrum Disorders - Ocak, Emre (Balkan Med J, 2018)
The etiology and the underlying pathogenetic mechanisms of autism spectrum disorders are still largely unknown. This article provides a comprehensive review of the studies that are relevant to autism spectrum disorders and central auditory processing disorders and also discusses the relationship between autism spectrum disorders and central auditory processing disorders in the light of recent studies on this subject, which may provide new pathways in a therapeutic perspective. Several studies confirm that most of the individuals with an autism spectrum disorder have some degree of sensory dysfunction related to disorders of processing auditory, visual, vestibular, and/or tactile stimuli. Among these studies, some have addressed central auditory processing disorders. There is an increasing amount of effort for studies regarding the link between autism spectrum disorders and central auditory processing disorders. Most of the studies investigating central auditory processing disorders in patients with autism spectrum disorders have used electrophysiological measurements such as mismatch negativity and P300 event-related potentials. In addition to these, several studies have reported deterioration in speech perception and expression in patients with autism spectrum disorders, which may also be related to central auditory processing disorders in this unique group of individuals.